2020
DOI: 10.1002/ehf2.12657
|View full text |Cite
|
Sign up to set email alerts
|

Android to gynoid fat ratio and its association with functional capacity in male patients with heart failure

Abstract: Aims We studied the association between android (A) to gynoid (G) fat ratio and functional capacity (peak VO 2 ) in male patients with heart failure with reduced ejection fraction (HFrEF). Methods and resultsWe enrolled 118 male patients with HFrEF with left ventricular ejection fraction (LVEF) <40%. Body composition (by using dual x-ray absorptiometry) and peak VO 2 (by cardiopulmonary exercise testing) were measured. Sarcopenic obesity was defined according to the Foundation for the National Institutes of He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
2
2
0
Order By: Relevance
“…The main finding of this study was that body fat mass (Android or Gynoid) was positively associated with BMD, regardless of gender (Males or Females) or sites (Femur or Lumbar spine), which was inconsistent with our hypothesis or conventional perception. Gender differences were found in body fat distribution, consistent with the previous studies [ 24 , 25 ]. In males, fat was more likely to be concentrated in the abdomen (Android fat), and in females, fat was more likely to be concentrated in the buttocks (Gynoid fat) [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The main finding of this study was that body fat mass (Android or Gynoid) was positively associated with BMD, regardless of gender (Males or Females) or sites (Femur or Lumbar spine), which was inconsistent with our hypothesis or conventional perception. Gender differences were found in body fat distribution, consistent with the previous studies [ 24 , 25 ]. In males, fat was more likely to be concentrated in the abdomen (Android fat), and in females, fat was more likely to be concentrated in the buttocks (Gynoid fat) [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the A/G ratio is linked to the progression of sarcopenia and inflammation. This could be related to the data observed in our patients [56]. Nevertheless, these findings should be interpreted with caution, since gynoid and android fat measures that are taken using older versions of DXA, as was the case in our study, do not distinguish between subcutaneous fat (orthotopic) and the ectopic fat in the abdominal muscle fascia, and the mesenteric fat surrounding organs and blood vessels [57].…”
Section: Discussionsupporting
confidence: 43%
“…Some studies have shown that gynoid fat mass, like android fat mass, was associated with increased cardiovascular risk ( 12 14 ) and various disease risks ( 15 , 16 ). It may also raise the burden on heart failure patients ( 17 ). However, a study reported that, android fat mass distribution is a risk factor for CVD, but gynoid fat mass distribution pattern is not, according to Kyoung-Bok Min et al ( 18 ).…”
Section: Introductionmentioning
confidence: 99%